Answer:
e
f
∘
g
(
x
)
=
2
x
2
−
4
x
−
3
And
g
∘
f
(
x
)
=
(
2
x
−
3
)
(
2
x
−
5
)
Step-by-step explanation: f
(
x
)
=
2
x
−
3
g
(
x
)
=
x
2
−
2
x
=
f
(
g
(
x
)
)
=
f
(
x
2
−
2
x
)
=
2
(
x
2
−
2
x
)
−
3
=
2
x
2
−
4
x
−
3
g
∘
f
(
x
)
=
g
(
f
(
x
)
)
=
g
(
2
x
−
3
)
=
(
2
x
−
3
)
2
−
2
(
2
x
−
3
)
=
(
2
x
−
3
)
(
2
x
−
3
−
2
)
=
(
2
x
−
3
)
(
2
x
−
5
)
f
∘
g
(
x
)
≠
g
∘
f
(
x
)
Answer: The b-value is the middle number, the number next to the X
Answer:
option A
Step-by-step explanation:
plz mark my answer as brainlist plzzzz . hope this will be helpful to you.
20& 10/35 - 26/35
19& 16/35 simplified to it's fullest.